Kritik Abdullah Saeed terhadap Praktik Pembiayaan Murabahah pada Bank Islam - Syaparuddin Syaparuddin (Islamica: Jurnal Studi Keislaman, 2012)
This paper is aimed at discussing the critical view of Abdullah Saeed as far as murabahah is concerned. For Saeed, this banking practice, which is adapted and adopted from Syari?ah has caused a lot of controversies. The basic question that a man like him asks is, does this Syari?ah banking system really make a difference? Nonetheless, it is this Syari?ah-based banking product that dominated the whole Islamic banking system in the great majority of Islamic countries. Investigating the nature of this product becomes therefore both strategic and important so as to have a better and proper understanding of it. This proper understanding will in turn influence the way this product is promoted and sold to the public in line with the values of Syari?ah. The paper will also compare murabahah with the similar banking practices in the conventional banks.